2018
DOI: 10.3791/57551
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides Produced by Selective Pressure Incorporation of Non-canonical Amino Acids

Abstract: Nature has a variety of possibilities to create new protein functions by modifying the sequence of the individual amino acid building blocks. However, all variations are based on the 20 canonical amino acids (cAAs). As a way to introduce additional physicochemical properties into polypeptides, the incorporation of non-canonical amino acids (ncAAs) is increasingly used in protein engineering. Due to their relatively short length, the modification of ribosomally synthesized and post-translationally modified pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Both residue-specific and site-specific approaches have been taken to incorporate ncAAs into proteins [ 62 ]. A residue-specific approach involves the feeding of amino acid analogues to nutritionally deficient strains to replace canonical residues without gene manipulation [ 63 ]. Derivatives of tryptophan, phenylalanine, proline and methionine have all been incorporated into target positions of nisin by selective pressure incorporation (SPI) [ 63 , 64 , 65 ].…”
Section: Nisin Variants Containing Noncanonical Amino Acidsmentioning
confidence: 99%
“…Both residue-specific and site-specific approaches have been taken to incorporate ncAAs into proteins [ 62 ]. A residue-specific approach involves the feeding of amino acid analogues to nutritionally deficient strains to replace canonical residues without gene manipulation [ 63 ]. Derivatives of tryptophan, phenylalanine, proline and methionine have all been incorporated into target positions of nisin by selective pressure incorporation (SPI) [ 63 , 64 , 65 ].…”
Section: Nisin Variants Containing Noncanonical Amino Acidsmentioning
confidence: 99%
“…The Schultz group incorporated several NSAAs into nisin by expressing the nisA encoding structural peptide, nisB encoding dehydratase, and nisC encoding cyclase with the coexpression of OTS for amber suppression in E. coli and found that αchloroacetamide-containing NSAA incorporation resulted in recombinant nisin variants with novel macrocyclic topologies (Zambaldo et al 2017). The Budisa group employed the selection pressure incorporation method to enable the residue-specific incorporation of six proline analogs into the antimicrobial peptide nisin (Nickling et al 2018). These researchers also produced bioactive nisin variants containing Nε-Boc-L-lysine both in Lactobacillus lactis and E. coli.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Our approach is based on multiple residue-specific incorporation of ncAAs in response to sense codons (sense codon reassignment), whereby within the target gene, the number of positions for Pro analog insertion can be manipulated via site-directed mutagenesis 44 . A similar approach was applied in our previous report on the preparation of recombinant peptides with antimicrobial properties 45 . In this work, we have applied the SPI method, which allows all proline residues to be replaced by related analogs, to generate proteins expected to possess distinct physicochemical properties not present in proteins synthesized with the canonical amino acid repertoire.…”
Section: Introductionmentioning
confidence: 99%